Chapter 10. The Ethics of Computing in Pharmaceutical Research (Computer Aided Drug Development, 2024)
AuthorMiss. Kajal AgrawalAssistant Professor, Department of Pharmaceutical Quality Assurance, Corporate Institute of Pharmacy, Bhopal, Madhya Pradesh, IndiaAbstractContemporary pharmaceutical research increasingly relies on computational methods, raising significant ethical considerations that demand careful attention from researchers, industry professionals, and regulatory bodies. This comprehensive examination explores the ethical dimensions of computing applications in pharmaceutical research, addressing crucial aspects such as data privacy, algorithmic transparency, and responsible innovation. The integration of artificial intelligence and machine learning in drug discovery and development introduces complex ethical challenges regarding bias, accountability, and validation of computational results. Particular emphasis is placed on protecting patient information, ensuring fair practices in automated decision-making, and maintaining the integrity of research outcomes. The discussion encompasses ethical frameworks for managing big data in pharmaceutical research, considerations for implementing AI systems, and guidelines for responsible innovation. Critical analysis of current practices reveals the need for balanced approaches that maximize technological benefits while upholding ethical principles.Keywords: Research Ethics; Computational Ethics; Data Privacy; Algorithms, AI in Pharmaceuticals; Digital EthicsView PDF